Desain Antenna Mikrostrip Pacth Rectangular MIMO Pada Frekuensi 15 GHz: Antena Mikrostrip - Wira Indani (Jurnal Elektro dan Mesin Terapan, 2021)
Cellular and wireless networks have developed rapidly in recent years. Long Term Evolution (LTE) based mobile broadband communication systems are currently used on a global scale providing network services to hundreds of millions of people. With the increasing number of users (users) and the need in the industrial sector such as the Internet of Things (IoT), reliable services and fast data transfer will be urgently needed. One of them is services on the 5G network at a frequency of 15 GHz. Where in this paper will discuss the Design of Rectangular MIMO Patch Microstrip Antenna at 15 GHz Frequency. The use of multiple antennas, in this case Multiple Input Multiple Output (MIMO), has an important role in 5G technology, due to the physical limitations of a small antenna. the antenna is thin but can work optimally at the expected frequency. From the results of the antenna design, the return loss value is -46.81 dB with a gain of 6.856 dBi. After the optimization process is carried out, the value obtained is in accordance with the problem limits to be achieved, namely the return loss value of -10 dB and the gain obtained is 6 dBi.